Регуляторна дія низькоінтенсивного видимого світла на сомітогенез птиці - Якименко, І.Л.; Цибулін, О.С. (Видавничий дім "Академперіодика" НАН України, 2007)
We research the influence of monochromatic red (λmax = 630 nm), blue (λmax = 470 nm), and green (λmax = 520 nm) light of laser light-emitting diodes on the early embryo development of Japanese Quail by the number of the differentiated pairs of somites which were generated by the 38-th hour of incubation. It is shown that red and blue lights at the intensity of a light beam of 0.1 mW/cm2 increases the number of the differentiated pairs of somites by 20.43% (and 15.18%, respectively) at the optimum temperature of incubation and by 27.62% (and 38.48%, respectively) at a lower temperature as compared with control group. A significant reduction of the number of the differentiated pairs of somites by 24.61% (31.26%) at the optimum temperature of incubation was observed at the intensity of red and blue lights of 1 mW/cm2. Green light at a similar intensity did not influence somitogenesis.